2014
DOI: 10.1111/jphp.12183
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between drugs and polymers influencing hot melt extrusion

Abstract: Objectives Hot melt extrusion (HME) as a technique for producing amorphous solid dispersion (ASD) has been widely used in pharmaceutical research. The biggest challenge for the application of HME is the thermal degradation of drug, poor physical stability of ASD and precipitation of drug during dissolution. Interactions between drugs and polymers may play an important role in overcoming these barriers. In this review, influence of drug-polymer interactions on HME and the methods for characterizing the drug-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 146 publications
(362 reference statements)
1
65
0
Order By: Relevance
“…It has been suggested that HME products need to be processed at an extrusion temperature (T ex ) approximately 30-60 o C higher than glass transition temperature (T g ) of the polymer to allow the polymer to have a viscosity low enough to allow extrusion (Chokshi et al, 2005;Li et al, 2014;McGinity et al, 2006). However, it is also necessary to consider the liquefaction of the drug within the processing apparatus, as the presence of a suspension would be expected to increase viscosity and hence impede processing.…”
Section: Hme Processability Of the Api-polymer Systemsmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been suggested that HME products need to be processed at an extrusion temperature (T ex ) approximately 30-60 o C higher than glass transition temperature (T g ) of the polymer to allow the polymer to have a viscosity low enough to allow extrusion (Chokshi et al, 2005;Li et al, 2014;McGinity et al, 2006). However, it is also necessary to consider the liquefaction of the drug within the processing apparatus, as the presence of a suspension would be expected to increase viscosity and hence impede processing.…”
Section: Hme Processability Of the Api-polymer Systemsmentioning
confidence: 97%
“…The issue of minimizing processing temperature via molecular interactions, which is itself related to miscibility, so as to reduce the risk of degradation has been highlighted by Li et al (2014) who discussed the possibility of extrusion at temperatures below the melting point of the drug via judicious use of interacting systems. Here we examine the role of such interactions in reducing the extrusion temperature below the Tg of the polymer itself with a concomitant view to examining the capacity for forming molecular dispersions using interactive and (effectively) non-interactive systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present formulation, it is imperative that the amalgamation of the polymers and the active substance happens to the best possible extent followed by melting of polymer blend and solubilization of drug substance [25][26][27] . Soluplus is a unique hydrophobic polymer with amphiphilic nature.…”
Section: Discussionmentioning
confidence: 99%